2011
DOI: 10.1371/journal.pntd.0001397
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Traditional and Revised WHO Classifications of Dengue Disease Severity

Abstract: Dengue is a major public health problem worldwide and continues to increase in incidence. Dengue virus (DENV) infection leads to a range of outcomes, including subclinical infection, undifferentiated febrile illness, Dengue Fever (DF), life-threatening syndromes with fluid loss and hypotensive shock, or other severe manifestations such as bleeding and organ failure. The long-standing World Health Organization (WHO) dengue classification and management scheme was recently revised, replacing DF, Dengue Hemorrhag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
191
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 191 publications
(210 citation statements)
references
References 16 publications
11
191
1
Order By: Relevance
“…Several studies [10,13,14] reported that the revised WHO classification is more sensitive as well as more or comparably specific in identifying severe cases. In contrast, some still indicate that WHO 1997 is more sensitive -though less specific -in capturing severe cases [15].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [10,13,14] reported that the revised WHO classification is more sensitive as well as more or comparably specific in identifying severe cases. In contrast, some still indicate that WHO 1997 is more sensitive -though less specific -in capturing severe cases [15].…”
Section: Discussionmentioning
confidence: 99%
“…The WHO (1986) and WHO (1997) case definition guidelines were grouped together during analysis, but were analysed separately from the WHO (2009) case definition guidelines due to reported differences Narvaez et al, 2011;Tsai et al, 2013a Odds ratios or statistical mean/median values could not be identified in most studies. No pooling was done given the extra sources of methodological diversity (types of prognostic factors being measured) and bias.…”
Section: Search Strategy and Data Extractionmentioning
confidence: 99%
“…We next sought to assess whether the QCF could be used to detect MBC and PB/PC responses in primary human PBMCs from DENV-infected individuals during either acute-or convalescentphase time points in participants in our Hospital-based Dengue Study in Nicaragua (11,23). PBMCs from a DENV-positive patient (secondary DENV3) were plated directly ex vivo and assessed via QCF to determine the PB/PC response.…”
Section: Optimization Of the Denv Qcfmentioning
confidence: 99%